Análise de acidentes fatais na indústria da construção civil do estado de Pernambuco - Maia, Diogo Coelho (2008)
One of the current themes within industry, particularly in civil construction, due to its dynamism, is how to minimize accidents, being fatal or otherwise, because in the event of these happening, it can be very costly. It is interesting to observe, that in relation to accidents, they are commented on in studies by Henrich in 1959 and Bird 1969, but that there is nothing specifically on civil construction. The closest to this area was the study caried out by Barkokébas et al. (2003) which comments on the cost of accidents. It can be observed from data from the Ministerio da Previdencia Social (2007), MPS that in 2006 R$ 4,44 million was paid to those who suffered accidents. In addition, it can be verified that in 2005 in the state of Pernambuco there 10.224 accidents in all industries, and that civil construction was responsible for 4,9% of this total. This research is of importance to civil construction to show, not only the numbers of professionals who suffer accidents, but also the points that need to research is to improved in the area of health and safety in this productive sector. The objective of this research is to indentify the causes of fatal accidents in the civil construction sector in the state of Pernambuco, in the period 2002 to 2006, through data from the Ministério do Trabalho e Emprego, to propose recomendations to reduce these tragedies. To achieve this quantitative and qualitative surveys of fatal acidents in the civil construction industry will be carried out together with MTE. After these surveys na analysis in the type of failure and the effect of event wil be carried out. Looking at the 5 (five) year periad in the civil construction sector, it can be seen that due to the lack or insufificient supervisin of activities, a lack or unsuitable analysis of the taskc together with other factors, 37 fatal accidents have ocorred during this period. Other than this, profissional with little time in the job suffer the most number of accidents